Professional potential of future primary school foreign language teachers: content, tasks, creativity - Tamara Marchii-Dmytrash (Vasyl Stefanyk Precarpathian National University, 2017)
The features of forming of future primary school foreign language teachers' professional potential are updated and justified in the article. The scientists' approaches to concretize the specific of professional potential are analyzed. It is proved, that the basis of the creative professional activities of a future teacher is the development of professional potential and individual style of activity, which are formed in higher educational institution. Key words: professional potential, foreign language teacher, primary school, creativity, creative activity, individual style, higher educational institution.